PENINGKATAN KAPASITAS DAN KUALITAS PRODUKSI PANGANAN BERBAHAN BAKU TALAS LOKAL PADA UMKM KITA BISA DI DESA SIDO MAKMUR KEPULAUAN MENTAWAI - Suliansyah, Irfan; B, Rini; Ekawati, Fitri; Hariandi, Doni (LPPM Universitas Andalas, 2025)
Taro is a viable source and holds potential as a supplement or substitute for rice/carbohydrates, as well as a raw material for flour production in the food industry. Taro plants possess significant economic value, as nearly all parts of the plant are edible. However, taro processing activities remain limited in terms of product variety, production continuity, target market, and marketing strategy. This programme aimed to enhance the understanding and skills of the partner in cultivating taro in accordance with Good Agricultural Practices (GAP), and to improve their capabilities in processing taro into various commercially viable products, as well as in packaging the resulting products. The activities were carried out at the 'Kita Bisa' Micro, Small and Medium Enterprise (MSME), located in Sido Makmur Village, North Sipora Sub-district, Mentawai Islands Regency, from July to November 2024. The methods employed included socialisation and technical assistance, focused on the priority issues identified within the partner MSME. Hands-on practice was also conducted, particularly in taro processing technology and product packaging techniques. The results demonstrated a notable improvement in understanding taro cultivation based on GAP, as well as enhanced skills and knowledge in processing taro into taro flour, taro cookies, and various-flavoured taro crisps. Additionally, there was a significant increase in the partner’s competence in packaging taro-based products. In conclusion, the programme was successfully implemented, resulting in measurable outputs that contributed to improvements in quality, quantity, and overall understanding among MSME members, spanning from cultivation to value-added product development.